Cultural competence in mental health care: a review of model evaluations - McKenzie Kwame; Edonya Patricia; Warfa Nasir; Bhui Kamaldeep; Bhugra Dinesh (BMC, 2007)
Abstract Background Cultural competency is now a core requirement for mental health professionals working with culturally diverse patient groups. Cultural competency training may improve the quality of mental health care for ethnic groups. Methods A systematic review that included evaluated models of professional education or service delivery. Results Of 109 potential papers, only 9 included an evaluation of the model to improve the cultural competency practice and service delivery. All 9 studies were located in North America. Cultural competency included modification of clinical practice and organizational performance. Few studies published their teaching and learning methods. Only three studies used quantitative outcomes. One of these showed a change in attitudes and skills of staff following training. The cultural consultation model showed evidence of significant satisfaction by clinicians using the service. No studies investigated service user experiences and outcomes. Conclusion There is limited evidence on the effectiveness of cultural competency training and service delivery. Further work is required to evaluate improvement in service users' experiences and outcomes.